The Epstein-Barr Virus Protein BRLF1 Activates S Phase Entry through E2F1 Induction - Swenson, Jennifer J. (American Society for Microbiology, 1999)
The Epstein-Barr Virus (EBV) immediate-early protein BRLF1 is one of two transactivators which mediate the switch from latent to lytic replication in EBV-infected cells. DNA viruses often modulate the function of critical cell cycle proteins to maximize the efficiency of virus replication. Here we have examined the effect of BRLF1 on cell cycle progression. A replication-deficient adenovirus expressing BRLF1 (AdBRLF1) was used to infect normal human fibroblasts and various epithelial cell lines. BRLF1 expression induced S phase entry in contact-inhibited fibroblasts and in the human osteosarcoma cell line U-2 OS. AdBRLF1 infection produced a dramatic increase in the level of E2F1 but not E2F4. In contrast, the levels of Rb, p107, and p130 were decreased in AdBRLF1-infected cells. Electrophoretic mobility shift assays confirmed an increased level of free E2F1 in the AdBRLF1-infected human fibroblasts. Consistent with the previously described effect of E2F1, AdBRLF1-infected fibroblasts had increased levels of p53 and p21 and died by apoptosis. BRLF1-induced activation of E2F1 may be required for efficient EBV lytic replication, since at least one critical viral replication gene (the viral DNA polymerase) is activated by E2F (C. Liu, N. D. Sista, and J. S. Pagano, J. Virol. 70:2545–2555, 1996).